Basic Life Support Training Methods for Knowledge and Skills: Systematic Literature Review - Tua Hutagaol; Ni Luh Widani (GLOBAL HEALTH SCIENCE GROUP, 2025)
Cardiac arrest is a medical emergency that requires immediate intervention to improve patient survival. Basic Life Support (BLS) training has proven effective in enhancing individuals’ knowledge and skills, particularly in cardiopulmonary resuscitation (CPR) techniques. However, challenges such as limited access, high costs, and skill deterioration over time remain significant obstacles. This study aims to evaluate various BLS training methods, including simulation-based approaches, technology-enhanced learning, and traditional methods. Articles searched via Google Scholar with a filter from 2019-2024 found 14 journal articles relevant to the research. A systematic literature review reveals that simulation-based training has the most substantial impact on improving practical skills compared to other approaches. Strategic recommendations include integrating BLS training into formal education curricula, conducting periodic refreshers, and utilizing innovative technologies to enhance training effectiveness. These measures are expected to improve the preparedness of both the public and healthcare providers in managing medical emergencies and ultimately save more lives.